2018
DOI: 10.1111/jcmm.13991
|View full text |Cite
|
Sign up to set email alerts
|

Why SNP rs227584 is associated with human BMD and fracture risk? A molecular and cellular study in bone cells

Abstract: A large number of SNPs significant for osteoporosis (OP) had been identified by genome‐wide association studies. However, the underlying association mechanisms were largely unknown. From the perspective of protein phosphorylation, gene expression regulation, and bone cell activity, this study aims to illustrate association mechanisms for representative SNPs of interest.We utilized public databases and bioinformatics tool to identify OP‐associated SNPs which potentially influence protein phosphorylation (phosSN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The functional enrichment analysis showed that Nek2 was mainly related to the 'autophagosome' and 'pyrimidine metabolism'. It had been shown that the over-expression of Nek2 was associated with the development of bone damage (36) and that it regulated osteoblast gene expression and affected osteoblast growth and activity (37). In addition, Nek2 induced osteoclast differentiation and bone destruction via heparanase in multiple myeloma (38).…”
Section: Discussionmentioning
confidence: 99%
“…The functional enrichment analysis showed that Nek2 was mainly related to the 'autophagosome' and 'pyrimidine metabolism'. It had been shown that the over-expression of Nek2 was associated with the development of bone damage (36) and that it regulated osteoblast gene expression and affected osteoblast growth and activity (37). In addition, Nek2 induced osteoclast differentiation and bone destruction via heparanase in multiple myeloma (38).…”
Section: Discussionmentioning
confidence: 99%
“…C17orf53 gene was associated with BMD and fracture risk in a large genome-wide meta-analysis study, including 17 GWAS and 32,961 individuals of European and East Asian ancestry (Estrada et al, 2012). A recent study investigated the molecular and cellular functions of a specific BMD-associated SNP (rs227584) in C17orf53 gene using osteoblastic cells and demonstrated that the SNP rs227584 may alter substrate-kinase interaction between protein C17orf53 and NEK2 and subsequently regulate osteoblast growth and activity (Zhou X. et al, 2019). Our findings complement the previous results and provide further supporting evidence for the significance of C17orf53 gene on regulating BMD variation and OP risk.…”
Section: Discussionmentioning
confidence: 99%